Creative methodologies of da’wah through different phases of a human’s life = Metodologi dakwah secara kreatif mengikut fasa kehidupan manusia - U Tun Aung, Maulana Akbar Shah (IIUM Press, International Islamic University Malaysia, 2018)
In addition to compliance with the five pillars of Islam, Da’wah Islamiyyah is an indispensable act for Muslims who view their life missions as to propagate Islam. The act of da’wah is a mission only undertaken by those who are selected to do so, as Allah SWT said: “You are the best of peoples, taken out for mankind, you enjoin what is right, forbid what is wrong…,” (Al-Qur’an, Al- `Imran, 3:110). The phrase “you are taken out for mankind” is a very clear phrase which refers to a special group. Many du’at propagate Islam through regular procedures. In this contemporary day and age, it would be more successful if creative da’wah methodologies are used to special groups where special talent is required. Examples of these special target groups are individuals such as [1] pregnant mothers, [2] mothers of new born babies, [3] parents of toddlers, [4] parents of children [5] youth, teenagers and adolescents, [6] married couples, [7] elderly or aged individuals and [8] non-Muslims. They are good targets to promote Islam. Thus, du’at must have special talents and knowledge to do so. In this regard, du’at must be equipped with exceptional knowledge of the target groups to propagate Islam effectively. The present paper attempts to highlight the distinctive natures of the above mentioned categories of individuals and explores how du’at should approach them when he or she encounters them for the purpose of promoting Islam.